It's What You Know: A Needs Assessment of MAT students' Social Studies Content Knowledge - Perrotta, Katherine; Keese, Jeffrey (The Teacher educator, 2025)
Although MAT pedagogy-only programs provide opportunities for career changers and college graduates with an expedited pathway into a teaching career while working and attending graduate school, there are concerns regarding whether these teachers possess strong subject matter knowledge. The purpose of this study is to examine MAT pedagogy-only middle and secondary social studies teachers' confidence levels in their content knowledge of general and specialized content-area topics in social studies. Our major findings show that their confidence levels are based upon their academic studies, experiential knowledge, and grade levels that they teach. Based on these findings, we recommend that education preparation providers offer content-area supports in the form of professional development and content-area tutoring to support MAT pedagogy-only students' content knowledge for middle and secondary social studies instruction.